Genome sequence and description of Pantoea septica strain FF5. Issue 1 (December 2015) - Lo, Cheikh; Padhmanabhan, Roshan; Mediannikov, Oleg; Nguyen, Thi; Raoult, Didier; Fournier, Pierre-Edouard; Fenollar, Florence
Abstract Strain FF5 was isolated from the skin flora of a healthy Senegalese 35-year-old woman. This strain was identified as belonging to the speciesPantoea septica based onrpoB sequence identity of 99.7 % withPantoea septica strain LMG 5345T and a highest MALDI-TOF-MS score of 2.3 withPantoea septica. LikeP. septica, this FF5 strain is a Gram-negative, aerobic, motile, and rod-shaped bacterium. Currently, 17 genomes have been sequenced within the genusPantoea but none forPantoea septica . Herein, we compared the genomic properties of strain FF5 to those of other species within the genusPantoea . The genome of this strain is 4, 548, 444 bp in length (1 chromosome, no plasmid) with a G + C content of 59.1 % containing 4125 protein-coding and 68 RNA genes (including 2 rRNA operons). We also performed an extensive phenotypic analysis showing new phenotypic characteristics such as the production of alkaline phosphatase, acid phosphatase and naphthol-AS-BI-phosphohydrolase.